P.027 Incidence of amyotrophic lateral sclerosis in Newfoundland and Labrador. (June 2019) - Aminian, KS; Whelan, G; Murphy, D; Stefanelli, M
Abstract : Background: There is a paucity of research regarding ALS epidemiology in Canada. Previously published data from Newfoundland and Labrador (NL) demonstrate an average incidence of 2.4/100, 000 from 2000-2004 (peak 3.3 in 2001, the highest reported in Canada). Local neurologists believe that the incidence has continued to increase. Methods: Clinicians affiliated with the electromyography (EMG) lab at the Health Sciences Centre in St. John's compiled a list of patients diagnosed with ALS from 2012-2016, based on recall. Their medical records were reviewed and demographic information collected. This was cross-referenced with new referrals to the ALS Society NL per year. Results: Based on new referrals to ALS Society NL the average incidence between 2012-2016 was 2.81/100, 000 (peak 3.6 in 2015). Average age-adjusted incidence from the EMG lab was 1.33 (peak 1.73 in 2016). The EMG lab documented a crude incidence of 3.97 in 2018. Conclusions: The incidence of ALS in NL is increased compared to the usual incidence of 1-2/100, 000 per year. After the preliminary study, the EMG lab maintained more thorough records and an incidence of 3.97/100, 000 was found in 2018. This makes a compelling argument for future research which could explore potential genetic or environmental causes for the increased incidence in this population.